Myasthenia Gravis: From the Viewpoint of Pathogenicity Focusing on Acetylcholine Receptor Clustering, Trans-Synaptic Homeostasis and Synaptic Stability - Takamori, Masaharu (Frontiers in Molecular Neuroscience, 2020)
Myasthenia gravis (MG) is a disease of postsynaptic neuromuscular junction (NMJ) where nicotinic acetylcholine (ACh) receptors (AChRs) are targeted by autoantibodies. Search for other pathogenic antigens has detected the antibodies against muscle-specific tyrosine kinase (MuSK) and low-density lipoprotein-related protein 4 (Lrp4), both causing pre- and post-synaptic impairments. Agrin is also suspected as a fourth pathogen. In a complex NMJ organization centering MuSK and related proteins, (1) the Wnt non-canonical pathway through the Wnt-Lrp4-MuSK cysteine-rich domain (CRD)-Dishevelled (Dvl, scaffold protein) signaling acts to form AChR prepatterning with axonal guidance; (2) the neural agrin-Lrp4-MuSK (Ig1/2 domains) signaling acts to form rapsyn-anchored AChR clusters at the innervated stage of muscle; (3) adaptor protein Dok-7 acts on MuSK activation for AChR clustering from “inside” and also on cytoskeletal dynamics to stabilize AChR clusters by the downstream effector Sorbs1/2; (4) the trans-synaptic retrograde signaling contributes to presynaptic organization for ACh release via i) Wnt-MuSK CRD-Dvl-β catenin-Slit 2 pathway, ii) Lrp4 and iii) laminins (α4, α5 and β2). The presynaptic Ca2+ homeostasis conditioning ACh release is modified by autoreceptors such as M1-type muscarinic AChR. The post-synaptic structure is stabilized by i) laminin-network including the muscle-derived agrin, ii) the extracellular matrix proteins (including collagen Q/perlecan and biglycan which link to MuSK Ig1 domain and CRD), and iii) the dystrophin-associated glycoprotein complex. The study on MuSK ectodomains (Ig1/2 domains and CRD) recognized by antibodies suggested that the MuSK antibodies were pathologically heterogenous due to their binding to functional domains. Focussing one of the matrix proteins, biglycan which functions in the manner similar to collagen Q, our antibody assay showed the negative result in MG patients. However, the synaptic stability may be impaired by antibodies against MuSK ectodomains because of the linkage of biglycan with MuSK Ig1 domain and CRD. Studies on a variety of signaling proteins may further provide a clue to understanding of pathogenic diversity of MG.